Sustainability improvement opportunities in Brazilian sectors: analysis of DEA slacks - Camioto, Flávia de Castro; Mariano, Enzo Barberio; Rebelatto, Daisy Aparecida do Nascimento (Brazilian Journal of Operations & Production Management, 2017)
The concept of sustainable production used in Camioto et al. (2014) evaluates the efficiency of Brazil’s industrial sectors from 1996 to 2009, taking into account energy consumption and respective contributions to the country’s economic and social aspects. In this article a replication of the performance of these sectors is conducted (Textile, Foods and Beverages, Chemical, Mining, Paper and Pulp, Nonmetallic and Metallurgical), from 1996 to 2010, with an in-depth analysis regarding the slacks between the current and the target performance in each variable relating to the sustainability analyzed. To determine these slacks, the SBM model of the Data Envelopment Analysis (DEA) method was used with the window analysis. The variables analyzed were energy consumption and fossil-fuel carbon emissions (inputs) and the Gross Domestic Product (GDP) per sectors, the persons employed and personnel expenses (outputs). The results showed that the variables which need the most changes to improve performance in all the sectors are the variables ‘persons employed’, followed by ‘fossil-fuel carbon emissions’, ‘Personnel expenses’, ‘Energy consumption’ and ‘GDP by sector’. It is expected that this study may provide a basis for future research and strategies to be implemented in other countries in order to guide the implementation of a more sustainable industrial policy.